Tree species used for fuelwood by remote indigenous communities in West Papua, Indonesia: Implication of empowerment program (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Indow L, Maturbongs RA, Prabawardani S, Hendri. 2022. Tree species used for fuelwood by remote indigenous communities in West Papua, Indonesia: Implication of empowerment program. Biodiversitas 23: 3507-3512. Fuelwood still contributes as an essential energy source for domestic uses especially in rural communities including in West Papua, Indonesia. While several development programs are implemented to enhance the life quality of rural indigenous communities, their implication for fuelwood use is not clear. This study aimed to identify fuelwood tree species used by communities in three villages in West Papua and to, assess its availability prior to the empowerment program and compare it to nowadays after the program based on the community's perspective. A descriptive method with qualitative and quantitative data components was used in this study. Data were collected at predetermined villages representing three ecological zones (i.e., Sakumi, Jamboi and Watitindau) using purposive sampling and semi-structured interviews with community representatives, tribal chiefs and leaders. The results showed that there were 5-7 plant species used as fuelwood, namely Piper aduncum, Casuarina equisetifolia, Rhizophora sp., Gliricidia sepium, Intsia bijuga, Pometia pinnata, Dodonaea viscosa, Homalium foetidum, Syzygium sp. and Muntingia calabura. These all-wood species have a good flame. Some high commercial tree species such as I. bijuga, P. pinnata and H. foetidum are only used in their branches and twigs for firewood. The local communities still use firewood despite the empowerment program since alternative fuel sources are not available or lacking, while the availability of firewood is plentiful. Nonetheless, in the long run, the continuous and extensive use of firewood will put pressure on the remaining trees and forest. Therefore, we recommend sustainably using firewood and replanting several species frequently used as firewood.